2020
DOI: 10.1097/j.pbj.0000000000000060
|View full text |Cite
|
Sign up to set email alerts
|

Anemia in preschool children from Angola: a review of the evidence

Abstract: Angola is one of the southern African countries with the highest prevalence of anemia, and despite the high geographic heterogeneity of its distribution across the country, it was reported to be indicative of a severe public health problem in some areas, mainly in children. Despite the relevance of this condition in the country there is still an important gap regarding scientific evidences and knowledge systematization in the indexed literature, that could be used to inform and optimize national public health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 106 publications
(201 reference statements)
0
4
0
Order By: Relevance
“…Extending that knowledge, the present study documents that children's age associates differently with IDA and Non-IDA and that gender possibly influence more the occurrence of IDA. Those differential associations may be related to different underlying factors of IDA and Non-IDA within those groups [49]. For instance, the increased risk of IDA observed in the 6-to-23-month group may be potentially related with the higher iron requirements in children within these age group, as also reported in other African studies [48].…”
Section: Prevalence Of Anaemiamentioning
confidence: 67%
See 1 more Smart Citation
“…Extending that knowledge, the present study documents that children's age associates differently with IDA and Non-IDA and that gender possibly influence more the occurrence of IDA. Those differential associations may be related to different underlying factors of IDA and Non-IDA within those groups [49]. For instance, the increased risk of IDA observed in the 6-to-23-month group may be potentially related with the higher iron requirements in children within these age group, as also reported in other African studies [48].…”
Section: Prevalence Of Anaemiamentioning
confidence: 67%
“…Regarding genotyping, we observed that 42.5% (195/459) of the females had at least one G6PD polymorphism (B/ 49, comparatively to having a normal genotype or having the sickle cell trait), associations that weren't observed for children in the same age group with IDA. In older children (aging between 24 and 36 months) the occurrence of IDA appeared to be associated with the number of residents in the same household (OR: 0.4, CI:0.15-0.83, for living with more than 5 residents), children being moderate-to-severely stunted (OR: 2.5, CI:1.14-5.50) and having inflammation (OR:4.3, CI: 1.69-11.02).…”
Section: Genetic Features Of Childrenmentioning
confidence: 84%
“…This is a very stretched and demanding target considering that the African region is a developing region with inadequate resources. A study conducted by Fancony et al [ 20 ] to understand the factors associated with anemia and the interventions implemented to prevent this condition showed that the progress of implementing interventions is slow and this may be due to different reasons including the economy. This indicates the necessity of collaboration to ensure the implementation of interventions is achieved.…”
Section: Introductionmentioning
confidence: 99%
“…A barefoot walking is very common in young children in sub-Saharan countries [22]. Other studies have suggested that deworming may also reduce anemia indirectly [23,24]. Tis can be seen in areas with a high prevalence of intestinal worms, where anemia is prevalent due to poor nutrition and low socioeconomic status, and not due to the direct efect of the parasites.…”
Section: Discussionmentioning
confidence: 99%